Computed tomography protocols optimization using non-prewhitening model observer. Issue 1 (February 2021) - Đedović, E; Faj, D; Bokulić, T
Abstract: The non-prewhitening model observer with eye filter (NPWE) allows assessing of performances of a whole imaging system, taking into account specific aspects of a considered clinical task and also the aspects of human visual system. The aim of this work is to determine the exposure parameters for computed tomography (CT) scan protocols so that they produce the satisfied performances of a human observer (HO). For each of the chosen scan protocols, the assessment of image quality parameters, based on the Fourier metric, as well as the volume CT dose index (CTDIvo l) measurements, have been performed. The scan protocols using the smooth reconstruction kernel, for an object diameter of 3 mm, 7 mm and 10 mm, and a contrast level of 20 Hounsfield units (HU) and 40 HU, gave the values of the area under curve (AUC) greater than 0.75 for CTDIvo l > 7.16 mGy. For a sharp kernel, all AUC values were smaller than 0.75 for all investigated scan protocols, object diameters and contrast levels. Through this work it was shown that the NPWE model-observer can be used as an effective and comprehensive optimization tool suitable for application in the various clinical tasks, considering also CTDIvo l values.